The development and evolution of human gene therapy - Friedmann, Theodore (Henry Stewart Talks, 2010)
Background in genetic concepts, Application by Sir Archibald Garrod to human disease, Discovery of the structure of DNA and new opportunities to understand and manipulate genes, Proof of principle of gene transfer into human cells using the Lesch Nyhan disease model, Rapid expansion of clinical gene therapy trials, high level of optimism and expectation, Major setback in human OTC gene therapy study, Patient death, Scientific and clinical success with another disease model, Severe combined immunodeficiency (SCID), Setback in SCID, Leukemia in some treated patients, Additional clinical successes, especially in Leber's congenital blindness